Pleural involvement in lung cancer - Agalioti, Theodora; Giannou, Anastasios D.; Stathopoulos, Georgios T. (Journal of Thoracic Disease, 2015)
The pleural space, a sterile secluded environment in the thoracic cavity, represents an attractive metastatic site for various cancers of lung, breast and gastrointestinal origins. Whereas lung and breast adenocarcinomas could invade the pleural space because of their anatomic proximity, “distant” cancers like ovarian or gastrointestinal tract adenocarcinomas may employ more active mechanisms to the same end. A pleural metastasis is often accompanied by a malignant pleural effusion (MPE), an unfavorable complication that severely restricts the quality of life and expectancy of the cancer patient. MPE is the net “product” of three different processes, namely inflammation, enhanced angiogenesis and vascular leakage. Current efforts are focusing on the identification of cancer cell autocrine (specific mutation spectra and biochemical pathways) and paracrine (cytokine and chemokine signals) characteristics as well as host features (immunological or other) that underlie the MPE phenotype. Herein we examine the pleural histology, cytology and molecular characteristics that make the pleural cavity an attractive metastasis destination for lung adenocarcinoma. Mesothelial and tumor features that may account for the tumor’s ability to invade the pleural space are highlighted. Finally, possible therapeutic interventions specifically targeting MPE are discussed.